Efficacy of palliative stenting in patients with esophageal obstruction attributable to malignancy - Yasuki Hatayama; Hideaki Ishigami; Hidehiro Kamezaki; Daisuke Murakami; Yukiko Shima; Kentaro Ishikawa; Harutoshi Sugiyama; Takayoshi Nishino; Makoto Arai (DEN Open)
Abstract Background Self‐expandable metallic stent (SEMS) placement is useful for patients with poor oral intake caused by esophageal stricture attributable to malignancy. In this study, we examined the usefulness of esophageal SEMS placement as a palliative treatment and evaluated the prognostic factors. Materials and methods Patients who underwent esophageal SEMS placement at three regional base hospitals from December 2007 to June 2023 were included in the study. Results Of 73 patients, 57 patients who underwent palliative SEMS placement were evaluated after excluding 16 patients in whom postoperative treatment was possible after SEMS placement. Median survival after SEMS placement was 67 days (mean, 96 ± 16 days). Univariate analysis identified age (≤78 years vs. >78 years), performance status (3 or 4 vs. 1 or 2), the cancer location (other sites vs. gastrointestinal cancer), the resumption of oral intake (failure vs. success), and clinical stage (IVA/IVB vs. III) as prognostic factors after SEMS placement. On multivariate analysis, performance status 3 or 4 (odds ratio [OR] = 2.87, 95% confidence interval [CI] = 1.28–6.45), cancers other than gastrointestinal cancer (OR = 3.75, 95% CI = 1.14–12.3), and failure to resume oral intake (OR = 21.3, 95% CI = 3.40–133.0) were significantly associated with poor prognosis. Conclusions Palliative treatment with SEMS placement was safe, and a high percentage of patients resumed food intake. An inability to resume food intake, poor performance status, and cancer outside the gastrointestinal tract were poor prognostic factors.